(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud Computing is a set of Information Technology Services, like network, software system, storage, hardware, software, and resources and these services are provided to a customer over a internet. These services of Cloud Computing are delivered by third party provider who owns the infrastructure. The advantages of cloud storage are easy access means access to your knowledge anywhere, anytime, scalability, resilience, cost efficiency, and high reliability of the data. Because of these advantages each and every organization is moving its data to the cloud, means it uses the storage service provided by the cloud provider. So it is required to protect that data against unauthorized access, modification or denial of services etc. Hence security of cloud means securing the operations and storage of the cloud providers. In this research paper, I propose an algorithm called Multilevel algorithm by using which an unauthorized user cannot access or modify the data or calculations of cloud. The work plan is to eliminate the concerns regarding data privacy using cryptographic algorithms to enhance the security in cloud as per different perspective of cloud customers